Automated solid‐phase extraction of phenolic acids using layered double hydroxide–alumina–polymer disks. Issue 9 (6th April 2018) - Ghani, Milad; Palomino Cabello, Carlos; Saraji, Mohammad; Manuel Estela, Jose; Cerdà, Víctor; Turnes Palomino, Gemma; Maya, Fernando
Abstract: The application of layered double hydroxide–Al2 O3 –polymer mixed‐matrix disks for solid‐phase extraction is reported for the first time. Al2 O3 is embedded in a polymer matrix followed by an in situ metal‐exchange process to obtain a layered double hydroxide–Al2 O3 –polymer mixed‐matrix disk with excellent flow‐through properties. The extraction performance of the prepared disks is evaluated as a proof of concept for the automated extraction using sequential injection analysis of organic acids ( p ‐hydroxybenzoic acid, 3, 4‐dihydroxybenzoic acid, gallic acid) following an anion‐exchange mechanism. After the solid‐phase extraction, phenolic acids were quantified by reversed‐phase high‐performance liquid chromatography with diode‐array detection using a core–shell silica–C18 stationary phase and isocratic elution (acetonitrile/0.5% acetic acid in pure water, 5:95, v/v). High sensitivity and reproducibility were obtained with limits of detection in the range of 0.12–0.25 μg/L (sample volume, 4 mL), and relative standard deviations between 2.9 and 3.4% (10 μg/L, n = 6). Enrichment factors of 34–39 were obtained. Layered double hydroxide–Al2 O3 –polymer mixed‐matrix disks had an average lifetime of 50 extractions. Analyte recoveries ranged from 93 to 96% for grape juice and nonalcoholic beer samples.